NEAR REAL-TIME MONITORING AND ALERT SYSTEM FOR EARTHQUAKE AND SEISMIC SIGNALS - ABDUL HALIM, MUHAMMAD HANIF (IRC, 2019)
The main objective of this project was to design the Near Real-time Monitoring and Alert System for Earthquake as a safety net system which has the capability to detect earthquake as well as any geological seismic signals. The project aims to come out with both software and hardware framework. The software is used to develop the block diagram and graphic user interface (GUI) whereas the hardware is used as the prototype casing. The objective of this project is to create a simulation of the earthquake vibration and user interface by using LabVIEW based on control system by collaborating the MEMS accelerometer sensor with Arduino microcontrollers. Besides, the system will also able to store the data for the later use by professionals working in this sector and send the collected data through the email. Moreover, the system is also able to determine the vibration level as the Magnitude Richter Scale by using the mathematical modeling with exponential and logarithmic produced by made-up vibration. All the data and graph will be displayed in LabVIEW which can be a user interface. The use of collected data for predicting the next earthquake from the people who responsible in processing data. This system is designed to react as soon as the p-wave come or primary wave across the sensors where this wave is the fastest wave created by an earthquake and first wave to be recorded by a seismograph. The user also may able to know the severity of the earthquake by observe the virtual alarm that was created in the system. Moreover, installing the GSM module on the hardware design is one of the future plans for making this project efficient in terms of alarming people from the devices. Therefore, this project could give an automatic alarm all by itself without the needs of earthquake engineer to monitor the system.